Accuracy assessment of a potential clinical use of navigation-guided intra-operative liver metastasis brachytherapy—a planning study - Herrmann, E. (Strahlenther Onkol, 2018)
For patients with inoperable liver metastases, intra-operative liver high dose-rate brachytherapy (HDR-BT) is a promising technology enabling delivery of a high radiation dose to the tumor, while sparing healthy tissue. Liver brachytherapy has been described in the literature as safe and effective for the treatment of primary or secondary hepatic malignancies. It is preferred over other ablative techniques for lesions that are either larger than 4 cm or located in close proximity to large vessels or the common bile duct. In contrast to external beam radiation techniques, organ movements do not affect the size of the irradiated volume in intra-operative HDR-BT and new technical solutions exist to support image guidance for intra-operative HDR-BT. We have retrospectively analyzed anonymized CT datasets of 5 patients who underwent open liver surgery (resection and/or ablation) in order to test whether the accuracy of a new image-guidance method specifically adapted for intra-operative HDR-BT is high enough to use it in similar situations and whether patients could potentially benefit from navigation-guided intra-operative needle placement for liver HDR-BT.